2007
DOI: 10.1177/0731684407079665
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Studies of Coir Fiber/Polyester and Glass Fiber/Polyester Composites under Different Conditions

Abstract: The influence of different conditions on the mechanical properties of short coir fiber reinforced polymer composites as well as glass fiber reinforced polymer composites have been analyzed and compared. Fiber length of 20 mm was found to be optimum for the best result. It is observed that the filler loading of 30 phr was most suitable for best results. Degradation studies were carried out in different solvents like 10% NaOH, 1 N HCl, and 10% NaCl and water. The effect of these solvents and water on the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 1 publication
6
38
0
2
Order By: Relevance
“…al [5] and its influence on mechanical properties was analyzed. It was observed that the tensile strength and the modulus (E) increases in acid environments and decreases for the other solvents.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…al [5] and its influence on mechanical properties was analyzed. It was observed that the tensile strength and the modulus (E) increases in acid environments and decreases for the other solvents.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In some studies, scanning electron microscopy or X-ray dispersion analysis was used. Other researchers [9][10][11][12][13] investigated the mechanical performance of coir fiber/thermoplastic polymer composites. The chopped dust [14,15] of coir fibers or coconut shells was also used with polymers to form composites.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Water absorption tests are carried out at different time periods under different climatic conditions such as cold at 10 o C, normal at atmosphere (25 o C) and hot at 60 o C [10]. The specimens are prepared based on ASTM D570 standards.…”
Section: Water Absorption Of Compositesmentioning
confidence: 99%
“…The fiber wetting was higher in higher fiber loading which increased the mechanical properties. Sindhu et al [10] investigated the coir fiber isophthalic polyester composites that were prepared with various fiber lengths at 30 % fiber loading. The stress versus strain curve of the composites gradually decreased with increasing the water aging period.…”
Section: Introductionmentioning
confidence: 99%